2015
DOI: 10.1503/cjs.012014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of cruciate-retaining total knee replacement in patients with rheumatoid arthritis: a minimum 15-year review

Abstract: Background:There is controversy about whether to retain or excise the posterior cruciate ligament in rheumatoid knees because attenuation of the ligament is often present in this subgroup of patients. We reviewed more than 15 years of results of cruciate-retaining total knee replacements (TKRs) in patients with rheumatoid arthritis. Methods:We reviewed patients' charts and radiographs to evaluate knee range of motion and flexion contractures, component loosening and osteolysis at the bonecement interface. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Improvements in RA medical therapy have markedly reduced the severity of symptoms in many, but RA patients continue to have a disproportionate need for surgery including arthroplasty surgery . Total knee replacement (TKR) is a frequent and efficacious treatment for RA patients with severe disease, designed to relieve joint pain whilst correcting deformity and enhancing mobility . The reported 10‐year survivorship of TKR in RA patients has a range of 81–97.7% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in RA medical therapy have markedly reduced the severity of symptoms in many, but RA patients continue to have a disproportionate need for surgery including arthroplasty surgery . Total knee replacement (TKR) is a frequent and efficacious treatment for RA patients with severe disease, designed to relieve joint pain whilst correcting deformity and enhancing mobility . The reported 10‐year survivorship of TKR in RA patients has a range of 81–97.7% …”
Section: Introductionmentioning
confidence: 99%
“…The current literature remains controversial with regards to prosthetic constraint that should be used for RA patients undergoing TKR. Many studies recommend the use of a cruciate substituting design while others have shown excellent results with cruciate retaining designs …”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that posterior instability due to PCL insufficiency is rarely the cause for revision in these patients [ 6 ]. Lee et al demonstrated excellent long-term survivorship at a minimum of 15-year follow-up with CR designs in RA patients and found no cases of revision resulting from PCL insufficiency [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change is noted in several studies across the globe, a 25 year follow up study from Mayo clinic demonstrated a good functional outcome score (mean score 79) at the end of 25 years [ 6 , 7 ]; a minimum 15 year follow up study from Korea noted an excellent post-operative functional score of 80 at final follow up [ 8 ]; a 12 year follow up study from Japan shows a good mean functional outcome score of 70 at final follow up [ 9 ]. These findings further reiterate the favourable long term functional status of cruciate retaining prosthesis.…”
Section: Review Of Clinical Analysismentioning
confidence: 91%
“…Cruciate retaining design is a less constrained prosthesis which allows better controlled femoral roll back than posterior stabilised design. Among the available literature Table 1 , the maximum average range of motion of 115 o was noted in a 22 year follow up study by Lee et al and correlates with the average knee ROM after TKA in OA patients [ 8 ]. The longest follow up study till date from Mayo clinic demonstrates an average knee ROM of 100 o [ 6 , 7 ].…”
Section: Review Of Clinical Analysismentioning
confidence: 99%